The effect of information technology capabilities and individual performance on organizational performance in Malaysia manufacturing industry - Lee, Khai Loon; Norhuda Dalya, Ab Razak (Penerbit UTHM, 2020)
Nowadays, Information Technology (IT) has become an essential individual and business. Farhanghi, Abbaspour, and Ghassemi (2013) state that IT is crucial for an organization's growth and survival. In the millennial era of the fast development of technology, changes absolutely provided the enormous impact of technological advancement.